Plasma volume reduction and hematological fluctuations in high-level athletes after an increased training load - Bejder, J.; Andersen, A. B.; Goetze, J. P.; Aachmann-Andersen, N. J.; Nordsborg, N. B. (Scandinavian Journal of Medicine & Science in Sports, 2017)
The time course of plasma volume (PV) reduction following an increased training load period is unknown and was investigated. The accompanying fluctuations in [Hb] and OFF-hr score were analyzed in the Athlete Biological Passport. Further, whether fluctuations in plasma albumin, soluble transferrin receptors (sTfR), and pro-atrial natriuretic peptide (proANP) concentrations correlate with PV fluctuations was investigated. Eleven high-level competitive cyclists were investigated for 3 weeks. After initial measurements in week 1, training load was increased ~250% in week 2 followed by a reversion to baseline training load in week 3. PV and hematological variables were determined frequently during all weeks. The higher training load in week 2 increased (P<.001) PV 10%, while [Hb] and OFF-hr score decreased ~6% (P<.01) and ~16% (P<.001), respectively. PV and [Hb] returned to baseline within 2 and 4 days after week 2, respectively, while OFF-hr score remained reduced for 6 days. Further, one and three atypical blood profiles of the ABP occurred during weeks 2 and 3, respectively. Individual changes in albumin, sTfR, and proANP only correlated weakly (R2<.20) with PV fluctuations. In conclusion, PV and [Hb] fluctuations caused by an elevated training load period were reverted within 2 and 4 days after returning to baseline training load, respectively, while OFF-hr remained altered for 6 days. Furthermore, some atypical blood profiles were induced during and subsequent to the increased training load, demonstrating the importance of knowledge on naturally occurring hematological fluctuations. Finally, concentrations of albumin, sTfR, and proANP could not explain PV fluctuations.